2018
DOI: 10.3989/gya.0350181
|View full text |Cite
|
Sign up to set email alerts
|

Quality preservation of walnut kernels using edible coatings

Abstract: The objective of this work was to evaluate the performance of various edible coatings for preserving the quality of walnut kernels (W) during storage. Three edible coatings based on carboxymethyl cellulose (CMC), methyl cellulose (MC) and whey protein isolates (WP) were prepared. Coated and uncoated walnuts (WC) were stored for 210 days at room temperature (23±2 °C). After 210 days, WC presented the highest peroxide value (PV = 3.06 meqO2/kg), conjugated dienes (CD = 3.01) and trienes (CT = 0.31), pentanal, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It is interesting to note that ECs contributed to hinder the intensity rating increase of this attribute. Grosso, Asensio, Nepote, and Grosso () also detected higher and lower astringency increments for uncoated walnuts and for coated walnuts with methyl cellulose, respectively. In contrast, Zhao and McDaniel () mentioned that certain ECs made from chitosan could increase the intensity of astringency in coated samples.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is interesting to note that ECs contributed to hinder the intensity rating increase of this attribute. Grosso, Asensio, Nepote, and Grosso () also detected higher and lower astringency increments for uncoated walnuts and for coated walnuts with methyl cellulose, respectively. In contrast, Zhao and McDaniel () mentioned that certain ECs made from chitosan could increase the intensity of astringency in coated samples.…”
Section: Resultsmentioning
confidence: 89%
“…The high‐protein content in the coating material was responsible for improving the coated peanut preservation (Grosso, Asensio, Nepote, & Grosso, , ). The method of DPF production led to a protein and carbohydrate content of 53.22g/100 g and 23.90 g/100 g, respectively (Riveros et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic responses of detected volatile compounds (peak area electronic counts: e.c.) were reported as a quantitative magnitude that indicates the evolution of the compounds in the different treatments during the storage study (Grosso, Asensio, Nepote, and Grosso, 2018a) and for those volatile compounds with a calibration curve, the quantification was also reported (µg/g).…”
Section: Methodsmentioning
confidence: 99%
“…Several coatings have been proven effective to extend nut stability because of their inherent physical barrier (i.e. passive) properties . Although the presence of antioxidants is expected to add an active role to coatings, some studies revealed that their presence did not enhance coating performance.…”
Section: Active Coatingsmentioning
confidence: 99%
“…passive) properties. 11,30,31 Although the presence of antioxidants is expected to add an active role to coatings, some studies revealed that their presence did not enhance coating performance. For instance, peanut oxidation was reduced by whey protein isolate coatings, but ascorbic palmitate and -tocopherol did not improve coating effectiveness.…”
Section: Active Coatingsmentioning
confidence: 99%